Exhibition of Tokyo Gallery 1971. (Tokyo : Tokyo Gallery, 1971)
Yoshinori Suzuki ; Shu Takahashi ; Ichiro Yamamato ; Etsutomu Kashihara ; Hiroshi Okada ; Ken Sakaki ; Hitoshi Nakazato ; U-Fan Lee ; Hisashi Indo ; Tatsuo Kondo ; Tadaaki Kuwayama ; Masaaki Yamada ; Masa Nagare
Exhibition of Tokyo Gallery 1971, Tokyo Gallery, Tokyo, 28 April - 11 May 1971
English-Japanese
kunstcatalogus
Keywords: Japan